Research on the Progress of Certification Regarding on Public Cloud Service - Feng Guo; Wei Li (Dianxin kexue)
The status quo of public cloud development at a global view was described,a lot effort into researching certification of cloud services in some developed countries were devoted,methodology and indicators for certification of public cloud were put forward,and suggestions related to the practice of certification of public cloud service in China were made.